Effects of deoxymugineic acid from rice root exudates on bacterial community composition in rhizosphere and root endosphere - YANG Linze; SHOU Huixia (浙江大学学报. 农业与生命科学版)
Under the iron-deficiency condition, roots of graminaceous plants secrete mugineic acids into the soil. To determine the effects of rice root exudate 2<alternatives>´<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/7572804D-D466-456d-893B-E89B64B779EB-M003c.jpg"/></alternatives>-deoxymugineic acid (DMA) on rhizosphere and root endosphere bacterial community, wild type rice named as Nipponbare and osbhlh156 and iro2 mutant rices that loss the ability to secrete DMA were used as experimental materials in this study. The rhizosphere and root endosphere microorganisms were sampled for DNA extraction and 16S rRNA gene amplicon sequencing and data analysis. The results showed that soil types and cultivation conditions had significant impacts on rhizosphere and root endosphere bacterial community composition. In contrast, the root exudate DMA had relatively less impact, but not negligible. The bacterial species and diversity decreased from rhizosphere to root endosphere, which confirmed that the root endosphere bacteria were gradually selected and colonized inside root by interacting with plants. Nine microbial taxa, including Bradyrhizobium and Dictyobacter, etc., were selected as biomarkers, to distinguish whether there is DMA secretion in the rice rhizosphere. Through functional prediction, it was found that the bacterial taxa with adenosine triphosphate-binding cassette (ABC) transporter function may be involved in plant iron transport and related function. This study clarifies the effects of DMA on the composition of rhizosphere and root endosphere bacterial community of rice and provides data support for the comprehensive analysis of the role of microorganisms in response to iron deficiency in rice.